Cholesterol, Atherosclerosis, and APOE in Vascular Contributions to Cognitive Impairment and Dementia (VCID): Potential Mechanisms and Therapy - Duong, Michael Tran; Nasrallah, Ilya M.; Wolk, David A.; Chang, Catherine C. Y.; Chang, Ta-Yuan (Frontiers in Aging Neuroscience, 2021)
Vascular contributions to cognitive impairment and dementia (VCID) are a common cause of cognitive impairment, yet limited therapies exist. This cerebrovascular disease causes neurodegeneration via acute, chronic, local, and systemic mechanisms. The etiology of VCID is complex, with significant impact from atherosclerosis. Risk factors including hypercholesterolemia and hypertension promote intracranial atherosclerotic disease and carotid artery stenosis, which disrupt cerebral blood flow and trigger ischemic strokes and VCID. Apolipoprotein E (APOE) is a cholesterol and phospholipid carrier present in plasma and various tissues. APOE is implicated in dyslipidemia and Alzheimer disease; however, its connection with VCID is less understood. Few experimental models for VCID exist so much of the present information has been drawn from clinical studies. Here, we review literature with a focus on clinical aspects of atherosclerotic cerebrovascular disease and build a working model for the pathogenesis of VCID. We describe potential intermediate steps in this model, linking cholesterol, atherosclerosis, and APOE with VCID. We posit that APOE4, a minor isoform of APOE, promotes lipid dyshomeostasis in astrocytes and microglia, leading to chronic neuroinflammation. APOE4 may also disturb lipid homeostasis in macrophages and smooth muscle cells, thus exacerbating systemic inflammation and promoting atherosclerotic plaque formation. Additionally, APOE4 may contribute to stromal activation of endothelial cells and pericytes that disturb the blood-brain barrier. These and other risk factors together lead to chronic inflammation and contribute to atherosclerosis, VCID, and neurodegeneration. Finally, we discuss potential cholesterol metabolism-based for future VCID treatment.